2008
DOI: 10.1375/jsc.3.1.57
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomised, Placebo-Controlled Trial of Cytisine for Smoking Cessation in Medium-Dependent Workers

Abstract: Among many studies on cytisine only a few have been controlled trials, and the aim of this study was to assess the efficacy of cytisine in a randomized controlled double-blind trial compared to placebo in medium-dependent smoking men working in mining industry. Materials and methods: 171 middle-aged smokers were randomised to either cytisine (25-days regimen) or placebo; both groups received individual counseling with brochure. Self-reported continuous abstinence was assessed at 8 and 26 weeks. Results: At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 11 publications
4
37
0
10
Order By: Relevance
“…They therefore did not combine the results of this study with the two more recent cytisine studies. 17,43 Their sensitivity analysis combining these three trials indicated substantial heterogeneity between this older study and the newer ones. Therefore, this study has not been included in the current report.…”
Section: Studies From Cahill Not Included In the Current Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…They therefore did not combine the results of this study with the two more recent cytisine studies. 17,43 Their sensitivity analysis combining these three trials indicated substantial heterogeneity between this older study and the newer ones. Therefore, this study has not been included in the current report.…”
Section: Studies From Cahill Not Included In the Current Reviewmentioning
confidence: 98%
“…No new trials of cytisine were identified, so that only two high-quality RCTs of cytisine with outcome data after a minimum follow-up of 6 months have been conducted to date. 17,43 A network meta-analysis was used to allow a comprehensive synthesis and comparison between smoking cessation treatments including cytisine, varenicline, nicotine patch and bupropion hydrochloride. A random (treatment)-effects model was used incorporating a log-log link function to allow for variation in the duration of follow-up between studies.…”
Section: Clinical Effectiveness Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytisine acts as similarly to varenicline, being a partial agonist of alpha4beta2 nicotinic acetylcholine receptors, responsible for reinforcing the effects of nicotine, also preventing nicotine from binding to these receptors, thus reducing the satisfaction and reward related to tobacco use, relevant negative withdrawal symptoms and cravings. 32,71,72 Tabex® is available in oral tablet form containing 1.5 mg cytisine and has been produced and marketed by the Bulgarian company Sopharma Pharmaceuticals since September 1964. 73 Tabex® was used for tobacco cessation for many decades on a national scale in the former Socialist countries, Bulgaria, Hungary, Poland, German Democratic Republic, Soviet Union being the first ever medication in human history officially approved for this purpose.…”
Section: Cytisinementioning
confidence: 99%
“…However, licensing and use of cytisine in other parts of the world did not develop for decades, in part due to the lack of evidence-based, more recently GCP compliant, trials. 71,74,75 The global search for tobacco cessation products with high availability, acceptability, efficacy and safety, combined with low cost, relevant for large scale cessation interventions within state supported programmes has recently boosted interest in cytisine.…”
Section: Cytisinementioning
confidence: 99%